2021
DOI: 10.5194/bg-18-487-2021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spatial variability on the exposure of fish to hypoxia: a modeling analysis for the Gulf of Mexico

Abstract: Abstract. The hypoxic zone in the northern Gulf of Mexico varies spatially (area, location) and temporally (onset, duration) on multiple scales. Exposure of fish to hypoxic dissolved oxygen (DO) concentrations (< 2 mg L−1) is often lethal and avoided, while exposure to 2 to 4 mg L−1 occurs readily and often causes the sublethal effects of decreased growth and fecundity for individuals of many species. We simulated the movement of individual fish within a high-resolution 3-D coupled hydrodynamic water qualit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…While hypoxic conditions are a major consideration, sublethal DO concentrations are also important. Many laboratory studies document that DO concentrations between 2 and 5 often result in less avoidance (i.e., significant exposure), and individuals show reduced growth and fecundity (Uphoff et al, 2011;LaBone et al, 2021). Our study showed that the presence of ARs would likely increase the exposure of the two rockfish species to 3 mg/ L. Therefore, both hypoxia and higher (moderate) DO concentrations should be part of the design and assessment of performance for ARs.…”
Section: Responses Of Reef-dependent Species To Changing Ocean Condit...mentioning
confidence: 66%
See 2 more Smart Citations
“…While hypoxic conditions are a major consideration, sublethal DO concentrations are also important. Many laboratory studies document that DO concentrations between 2 and 5 often result in less avoidance (i.e., significant exposure), and individuals show reduced growth and fecundity (Uphoff et al, 2011;LaBone et al, 2021). Our study showed that the presence of ARs would likely increase the exposure of the two rockfish species to 3 mg/ L. Therefore, both hypoxia and higher (moderate) DO concentrations should be part of the design and assessment of performance for ARs.…”
Section: Responses Of Reef-dependent Species To Changing Ocean Condit...mentioning
confidence: 66%
“…In large-scale sea areas, hypoxic conditions may change gradually and can be distributed in patches (LaBone et al, 2021). A relatively stationary and stable low-oxygen location allows most organisms, especially fish, to avoid this area.…”
Section: Effects Of Artificial Reef On Exposure To Low Oxygenmentioning
confidence: 99%
See 1 more Smart Citation
“…Such simplifying assumptions are common in ecosystem models. Examples include ignoring changes in all but one or two activities in response to hypoxia and the aggregation of several activities into a higher order process such as growth (Karim et al, 2003;de Mutsert et al, 2016;LaBone et al, 2021). This is a valid approach which provides valuable insight into fish population and community response to hypoxia.…”
Section: Introductionmentioning
confidence: 99%